World market prices hit coffee farmers - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Prices for coffee have dropped dramatically from 0.95 $US in September 2000 to 0.49 $US/ lb in March 2001. According to the Association of Coffee Producing Countries (ACPC), excessive availability of low-grade material, production increases and high...